Navigating Liminal Space: Embodied Knowledge within Performance Pedagogies in Archival Reconstruction - Ramsay, Fiona (University of the Witwatersrand, Johannesburg, 2024)
I am a performing artist and actor existing in a liminal space because although I am African (in that I was born in, live, and work in Africa), I am caught in an in- between space, somewhere on a continuum straddling Western and African heritages. My practice developed in a culturally complicated context during the 1970s, 1980s and 1990s in South Africa amid turbulent social tensions and complex, intricate and problematic interactions in a culturally divided society within a political system that legally prohibited cultural engagement. I revisit the archive of my work that emerged during my career to examine the methodology which developed and interrogated the shifts and attempts toward a decolonised practice. Awareness of cultures beyond our own can advance comprehensive views of humanity, promote cultural sensitivity and an appreciation of diversity, encourage rigorous critical thinking by questioning stereotypes, increase global connection and contribute to inclusive decolonised curricula. I am situated in this complicated space on a continuum between identities, and I acknowledge this has contributed to my practice. The premise of becoming or transforming into an ‘other’ is a fundamental principle and skill of acting in the tradition I was schooled in but less valued in others. Reflecting on the archive of my work, I examine the process that developed and analysed both broad liminal spaces and more focused liminal nodes that facilitate transformations to inhabit and perform various roles. I investigate the disruptions that occur in these when accessing unfamiliar cultural frames. Theatre, specifically, and the arts, more generally, are partly derived from borrowing or laying claim to previous discoveries, and my archive reflects the work out of which my practice has grown. I navigate this continuum and exist in and not independently from this Western and African complexity. I raise contemporary issues that share relationships with theories of identity and a complicated political history. I examine how these shape my practice and how the findings may be included and contribute to developing and refining teaching methods and curricula in the postcolony.
A research report Submitted in fulfillment of the requirements for a Doctor of Philosophy, Theatre and Performance, In the Faculty of Humanities , School of Arts, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Art; character; culture; ethnicity; identity; language; liminal space; personality; self and selves; tradition; voice; SDG-4: Quality education